2013
DOI: 10.3938/jkps.62.569
|View full text |Cite
|
Sign up to set email alerts
|

Random matrix theory and cross-correlations in global financial indices and local stock market indices

Abstract: We analyzed cross-correlations between price fluctuations of global financial indices (20 daily stock indices over the world) and local indices (daily indices of 200 companies in the Korean stock market) by using random matrix theory (RMT). We compared eigenvalues and components of the largest and the second largest eigenvectors of the cross-correlation matrix before, during, and after the global financial the crisis in the year 2008. We find that the majority of its eigenvalues fall within the RMT bounds [λ_,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…The market correlation structure changes around financial crashes. The average correlation after the critical point of crash is higher than that before the crash [3,17,24]. Also, the correlation network becomes more connected after the crash [25].…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The market correlation structure changes around financial crashes. The average correlation after the critical point of crash is higher than that before the crash [3,17,24]. Also, the correlation network becomes more connected after the crash [25].…”
mentioning
confidence: 85%
“…-Financial markets evolve in a selforganized manner with the interacting elements forming complex networks at different levels, including international markets [1][2][3][4], individual markets [5][6][7][8], and security trading networks [9][10][11][12][13][14][15][16]. There are well-documented stylized facts of stock return time series within individual markets unveiled by the random matrix theory (RMT) analysis [6,17]: (1) The largest eigenvalue reflects the market effect such that its eigenportfolio returns are strongly correlated with the market returns; (2) Other largest eigenvalues contain information of industrial sectors; and (3) The smallest eigenvalues embed stock pairs with large correlations.…”
mentioning
confidence: 99%
“…In 2012, Livan and Rebecchi [13] used daily prices of stocks belonging to the stock exchanges of the USA and of the UK, and looked for the emergence of correlations between the two markets in the eigenvalue spectrum of their non symmetric correlation matrix, also considering time-lagged correlations over short lags. In 2013, Nobi, Maeng, Ha, and Lee [14] used same-day cross-correlations in order to study some global and local financial market indices; Li [15] found that asymmetric comovements between upturns and downturns of stock markets exist between the USA stock market and the stock markets of Canada, France, Germany, and the United Kingdom, but not necessarily between the USA stock market and the Japanese stock market.…”
Section: Introductionmentioning
confidence: 99%
“…The network has emerged as a crucial framework in biological networks when researchers study and analyze an open and novel problem in complex systems [1][2][3][4]. The most important properties of biological networks are the structural and the topological ones involving interacting amino acids.…”
Section: Introductionmentioning
confidence: 99%